Eksplorasi Peran Front Office dalam Menciptakan Kepuasan dan Loyalitas Tamu di Hotel The Manohara Yogyakarta - Fera Dhian Anggraini; Fendi Kurniawan (JURNAL NUSANTARA, 2025)
The hospitality industry positions the Front Office department as the frontline of service that interacts directly with all guests. This study aims to explore the role of the Front Office in creating guest satisfaction and loyalty at The Manohara Hotel Yogyakarta using a qualitative case study approach. Data were collected through in-depth interviews, observations, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The results indicate that the role of the Front Office department is highly complex, encompassing administrative responsibilities, interpersonal communication, empathy, complaint handling, and service personalization. Responsive and professional interactions significantly contribute to the formation of guest satisfaction, which in turn impacts loyalty, as reflected in revisit intentions and positive recommendations.